Influence of Intercropping on Eugenia dysenterica (Mart.) DC. Fruit Quality - Almeida, Micael Jose de [UNESP]; Dornelles, Paulo; Rezende, Thaisa Alves Matos de; Silva, Ludiele de Lima da; Silva, Fabiano Guimarães; Duarte, Larissa Graziele Rauber; de Oliveira Filho, Josemar Gonçalves; Egea, Mariana Buranelo (MDPI, 2024)
Intercropping to integrate cover crops with fruit trees in the Brazilian Cerrado is an innovative strategy for creating a more sustainable food system. This agricultural practice contributes to maintaining soil quality and improves fruits’ chemical and technological properties, such as those of Eugenia dysenterica (Mart.) DC. (cagaita). Given the significant fruit production potential of the Brazilian Cerrado, this study aimed to investigate the impact of an intercropping system involving cagaita trees and various cover crops, specifically Calopogonium mucunoides Desv. (CA), Crotalaria juncea (CR), Lablab purpureus (L.) Sweet (LA), brachiaria (Brachiaria decumbens L.) + nitrogen source (urea) (BRN), and brachiaria (Brachiaria decumbens L.) (BR), on the chemical composition, technological properties, and morphological characteristics of cagaita fruits. Treatments involving leguminous cover crops (CA, LA, and CR) significantly increased nitrogen (N) levels in cagaita fruits, comparable to those observed with the BRN treatment. However, the treatment utilizing BR resulted in the highest levels of macrominerals (Ca, Mg, and K), which are essential for meeting the Recommended Dietary Intake (RDI) and demonstrated a notable positive impact on pulp yield (>78%). Additionally, the antioxidant potential and phenolic content were the highest in the BR, CA, and LA treatments, with the lowest levels recorded for the CR treatment. This study underscores the importance of sustainable agricultural practices in the Brazilian Cerrado, demonstrating their potential to enhance the nutritional quality (both micro and macronutrients), technological properties, and overall development of Eugenia dysenterica DC. fruits, thereby adding value to food and contributing to a more resilient and productive food system.
Keywords: bioactive compounds; cagaita; Cerrado; intercropping; nutritional quality